Volcanoes & earthquakes - "Knight, Linsay" (Time Warner Books Hong Kong, 1996)
Part of the Nature Company Discoveries Library. Atmospheric illustrations, strong photographs, and lively text engage and encourage readers to discover for themselves the world around them. Includes a four-page foldout that reveals a dramatic perspective